COMMUNITY PERCEPTIONS OF THE FULFILLMENT OF NUTRITIONAL NEEDS THROUGH THE CONSUMPTION OF OYEK STAPLE FOOD IN CEMORO VILLAGE, TEMANGGUNG REGENCY. - Indra Resya Afani; Agustinus Sugeng Priyanto; Puji Lestari; Hafiz Rafi Uddin (Unnes Civic Education Journal, 2026)
Fulfilling nutritional needs is a fundamental human right essential for achieving a healthy and prosperous life. In Cemoro Village, Temanggung Regency, some residents continue to consume Oyek, a traditional corn-based staple food, as part of their daily diet despite the increasing preference for rice due to its convenience. This study aims to analyze community perceptions of fulfilling food and nutrition rights through Oyek consumption and identify the social, cultural, and dietary factors influencing these perceptions. A qualitative descriptive approach was employed using interviews, observations, and documentation involving Oyek consumers, village officials, Posyandu cadres, and nutritionists. Data were analyzed using the Miles and Huberman interactive model. The findings indicate that Oyek contributes to fulfilling nutritional needs and reflects local wisdom while supporting household food security. Community perceptions are shaped by sociological, anthropological, geographical, nutritional, and human rights perspectives, as well as local culture and generational differences. Based on Social Cognitive Theory, Oyek consumption results from interactions among personal, environmental, and behavioral factors. Older generations primarily maintain Oyek as a cultural heritage and energy source, whereas younger generations tend to consume it for health and dietary reasons. Overall, Oyek remains a valuable local food that supports nutrition, food security, and cultural preservation in rural communities.